2021
DOI: 10.1101/2021.05.19.444711
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cellulonodin-2 and Lihuanodin: Lasso Peptides with an Aspartimide Post-translational Modification

Abstract: Lasso peptides are a family of ribosomally synthesized and post-translationally modified peptides (RiPPs) defined by their threaded structure. Besides the class-defining isopeptide bond, other post-translational modifications (PTMs) that further tailor lasso peptides have been previously reported. Using genome mining tools, we identified a subset of lasso peptide biosynthetic gene clusters (BGCs) that are colocalized with protein L-isoaspartyl methyltransferase (PIMT) homologs. PIMTs have an important role in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…32,37 The addition of an electrophilic moiety like the succinimide to such inhibitors could convert them into suicide inhibitors that covalently attach to a protease target. In addition to OEPs as described here, this novel class of Asp-modifying O-methyltransferases has also been found in lasso peptide BGCs (see companion paper by Cao et al) 47 as well as in lanthipeptide BGCs. 65 While all three examples of these RiPP modifying methyltransferases start off with Asp methylation and formation of aspartimide, the fate of the aspartimide residue differs.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…32,37 The addition of an electrophilic moiety like the succinimide to such inhibitors could convert them into suicide inhibitors that covalently attach to a protease target. In addition to OEPs as described here, this novel class of Asp-modifying O-methyltransferases has also been found in lasso peptide BGCs (see companion paper by Cao et al) 47 as well as in lanthipeptide BGCs. 65 While all three examples of these RiPP modifying methyltransferases start off with Asp methylation and formation of aspartimide, the fate of the aspartimide residue differs.…”
Section: Discussionmentioning
confidence: 55%
“…46 In a closely related organism, Thermobifida cellulosilytica, there is a lasso peptide biosynthetic gene cluster (BGC) with an Omethyltransferase in addition to the minimal biosynthetic genes for lasso peptides. 47 We searched T. fusca for similar O-methyltransferases and found one associated with an ATP-grasp enzyme and a putative RiPP precursor. In a previous bioinformatic survey of ATP-grasp enzyme prevalence, the colocalization of an ATP-grasp enzyme, an O-methyltransferase, and a precursor protein was noted in actinobacteria.…”
Section: A Microviridin/oep-like Bgc In T Fusca Harbors An Uncharacte...mentioning
confidence: 99%
“…Members of this family are related to IPR000682, which converts Lisoaspartyl and D-aspartyl residues to L-Asp, and IPR027573, which frequently co-occurs with lanthipeptide biosynthetic enzymes. 34 Recently, members of the latter family, OlvS A , TceM, and LihM, were implicated in RiPP biosynthesis 35,36 OlvS A catalyzes a three-step reaction (methylation, cyclization, and hydrolysis) of a highly conserved L-Asp to the corresponding L-isoaspartyl residue in OlvA, the cognate lanthipeptide precursor peptide. TceM and LihM introduce stable aspartimide moieties in the lasso peptides, cellulonodin-2 and lihuanodin, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…22 RiPP-associated PIMTs also harbor an additional Cterminal domain of >100 aa relative to canonical PIMTs. In our previous work on the PIMT homologues that aspartimidylate lasso peptides, 20 we showed that this C-terminal extension to PIMT is important for RiPP substrate recognition.…”
Section: ■ Introductionmentioning
confidence: 82%